An empirical study on the relationship among IT capabilities, business process and firm's performance. (27th December 2021) - Pandya, Kaushik V.; Sukumar, Arun; Jafari-Sadeghi, Vahid; Tomlins, Richard
This study investigates the influencing mechanism between IT capabilities and the firm's performance. We believe that business process is the principal factor and suggest that IT capabilities improve business process and subsequently enhance the firm's performance. The study of the underlying factors among IT capabilities, business performance, and firm's performance is considered rare and although some researchers have introduced conceptual models and empirical tests, they are not able to support the cumulative model. It is found out that IT capabilities have a significant and positive relationship to the firm's performance. Besides, business process reengineering, and process efficiency contribute more to this relationship by mediating effect. This study will benefit business researchers, strategic researchers and managers in various industries because this will contribute to a better understanding of IT capabilities, business process, and firm's performance to a greater extent and provide fundamentals for strategic decisions in IT investments of a firm.